Testing the moderating role of contextual ambidexterity on the relationship between behavioral integration processes of the top management team and organizations' : orientation toward sustainable performance (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The current research aims to test the interactive variable (contextual ambidexterity) with its dimensions: exploratory competencies and exploitative competencies for the relationship between the behavioral integration processes of the senior management team and the direction of the University of Kufa towards achieving sustainable performance from the point of view of the academic leaders working in it through an exploratory study. In order to reach the results expected from the research The researchers relied on a purposeful sample of academic leaders who work at the University of Kufa, and using an electronic questionnaire on (90) individuals to obtain data on the practical side and conduct statistical analysis to test the research hypotheses, as they were analyzed according to the least squares modeling method (PLS-SEM) using the advanced statistical program. (SmartPLS v.3), and Microsoft Excel, 2010) to organize and examine data. The study came out with a set of conclusions, the most important of which are: the existence of positive influence relationships for the behavioral integration processes of the administrative leaders of the University of Kufa and their orientation towards sustainable performance, and for contextual ambidexterity in its two dimensions (exploratory ambidexterity and exploitative ambidexterity). Enhancing effect of the positive relationship of behavioral integration processes for the administrative leaders of the researched university and their orientation towards sustainable performance. The study also presented a set of proposals to decision-makers that would raise the level of behavioral integration processes and activate the requirements for performance sustainability.